Classroom Management in the Implementation of Learning Systems in Schools - Jose A. Sarmento; Jacinto Junior (Southeast Asian Journal of Global Trends and Issues in Education, 2025)
Classroom management is an aspect of education that is often the main concern of professional teachers, teachers play a major role in the development of education, especially those held formally in schools. Classroom management is an important factor in the success of teaching and learning activities. Activities undertaken by a teacher to create a conducive classroom atmosphere and situation in every learning activity are very vital. Teachers also determine student success, especially those related to the learning process. Creating a comfortable learning quality is part of classroom management. The purpose of this study was to determine how classroom management is applied to improve the effectiveness of the learning process. Learning will not be carried out effectively if educators are unable to manage the class properly. Classroom management plays an important role in the development and character of students, in learning planning it must be planned by educators so that learning performance runs in one direction. The scope of the school affects learning performance, in this case educators must be able to interact well between educators and students. Classroom management in the learning process is carried out through several approaches, principles, and components. There are factors that influence the scope of the class such as curriculum, students, and academics.